2009
DOI: 10.1159/000255162
|View full text |Cite
|
Sign up to set email alerts
|

Cord Blood Cardiac Troponin T and Nonprotein-Bound Iron Levels in Newborns of Mild Pre-Eclamptic Mothers

Abstract: Background: In hypoxic newborns, cardiac troponin T (cTnT) was shown to be an indicator of cardiac damage and increased levels of nonprotein-bound iron (NPBI), an indicator of increased free radical production and perinatal brain damage. Objective: The aim of this study was to determine cord blood cTnT and NPBI levels in neonates of mild pre-eclamptic mothers. Methods: The study included 50 babies of mild pre-eclamptic mothers and 50 babies of healthy mothers. cTnT and NPBI levels were measured in cord blood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…Although our study supports the existing data linking troponin T and gestational age at delivery, birth weight, APGAR scores, and umbilical artery Doppler PI, Karadeniz et al (14) . certified no relationship between troponin T and gestational age or birth weight in fetuses with mild pre-eclampsia.…”
Section: Discussionsupporting
confidence: 85%
“…Although our study supports the existing data linking troponin T and gestational age at delivery, birth weight, APGAR scores, and umbilical artery Doppler PI, Karadeniz et al (14) . certified no relationship between troponin T and gestational age or birth weight in fetuses with mild pre-eclampsia.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies suggested biochemical changes in preeclampsia or IUGR: Karadeniz et al . reported that increased levels of cardiac troponin T (cTnT) in cord blood may be a biochemical marker of cardiac involvement in babies of mild preeclampsia; modified‐myocardial performance index, blood B‐type natriuretic peptide, and early‐to‐late diastolic filling ratios were increased in IUGR fetuses in a stage‐dependent manner; SGA infants had detectable cardiac troponin I in umbilical cord blood, which may predispose to the development of adult premature cardiovascular disease and death . To our knowledge, there are few related reports on the potential TDI appliance in co‐effect of preeclampsia and IUGR on fetal cardiac function, despite that Comas et al .…”
Section: Discussionmentioning
confidence: 99%
“…3 A growing body of evidence suggests that fetal cardiac impairment may be evident in preeclampsia; several investigators have previously documented the presence of fetal cardiac dysfunction [4][5][6] and increased cardiac troponin T in cord blood in preeclampsia. 7 Also, cardiac dysfunction may continue during postnatal life, with reports that children born from pregnancies complicated by preeclampsia may demonstrate cardiac dysfunction from ages 5 to 8 years old. 8 It is unclear whether IUGR has a synergistic effect with preeclampsia on cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Tocolytic therapy with β-sympathomimetics was related to an elevation in cTnT in the neonate (39). Elevated levels of cTnT were found in infants born to mothers who experienced preeclampsia, thereby associating maternal disease with neonatal myocyte compromise (40). Makikallio et al found that cTnT levels were elevated in infants born after severe placental insufficiency, although other studies failed to show an increase in cTnI levels during intrauterine growth restriction (35,41).…”
Section: Clinical Indicationsmentioning
confidence: 99%